Occupational Frostbite in a Myanmar Worker in Thailand: A Case Report - Laorattapong, Apisorn; Poobunjirdkul, Sarun (Journal of Preventive Medicine Association of Thailand, 2025)
A 24-year-old male from Myanmar working in a cold storage facility presented with symptoms of frostbite. The patient experienced numbness, pain and discoloration in both hands after working continuously for 4 hours in a cold storage room at -18°C, contrary to workplace policy, which requires alternating one-hour shifts. Initial symptoms included redness, swelling, and clear blisters, which progressed to darkened finger discoloration. The diagnosis was confirmed as second-degree frostbite based on clinical examination, patient history, and occupational exposure. Environmental assessments supported the workplace risk due to prolonged cold exposure and suboptimal adherence to safety protocols. Differential diagnoses, including Buerger's disease, were ruled out based on the absence of a smoking history or vibration exposure. The conclusion from the Nine Steps in Occupational Diseases Diagnosis suggests that frostbite is work-related. A review of the literature reveals that reports of cold-related illnesses in Thailand are still limited. The authors, therefore, present a case of frostbite occurring in a factory in Thailand.